THE NEW RETAIL PARADIGM - MANAGING CHANGE IN RETAIL INDUSTRY THROUGH SUPPLY CHAIN AND TECHNOLOGY - Muhammad Ikhwan Mohamed Suhaimi (Tesis, 2021)
This study therefore examines the strategies of supply chain retailers, economies, store operations and inventories of customers facing store technology resulting from the visit of flagship stores in Malaysia.